HIV Progression Depends on Codon and Amino Acid Usage Profile of Envelope Protein and Associated Host-Genetic Influence - Roy, Ayan; Banerjee, Rachana; Basak, Surajit (Frontiers in Microbiology, 2017)
Acquired immune deficiency syndrome (AIDS) is a spectrum of conditions caused by infection with the human immunodeficiency virus (HIV). Two types of HIV have been characterized: HIV-1 and HIV-2. The present study investigated whether evolutionary selection pressure differs between rapid progressor (RP), slow progressor (SP) and long-term non-progressor (LTNP) of HIV-I infected individuals. An unexpected association between the evolutionary rate of substitution in envelope (env) gene and disease progression is observed. Our present study suggests that env genes of LTNP are subject to unusually strong functional constraint with respect to RP. We also observed that the three categories of env genes i.e., RP, SP and LTNP, had their own characteristic pattern of amino acid usage and SP and LTNP sequences shared similar patterns of amino acid usage different from RP sequences and evolutionary rate significantly influenced the amino acid usage pattern of the three different types of env gene sequences. It was also noted that the evolutionary rate for the glycosylation sites of LTNP and SP sequences were even significantly less than the RP sequences. Comparative analysis on the influence of human host on the three categories of env genes are well correlated with the rates of disease progression suggesting the adaptive strategies of the viruses for successful residence and infection. Host associated selective constraints appeared most relaxed on the RP sequences and strongest in LTNP sequences. The present study clearly portrays how evolutionary selection pressure differs between three categories of env genes i.e., RP, SP and LTNP. The env genes, coding for the envelope glycoproteins, experience severe selection constraints from the host due to their constant exposure to the host immune system. In this perspective it might be suggested that env gene evolution occurs mainly by negative selection with the occurrence of mutation that might not reach fixation in the viral population. This work also confers a deeper insight into the crucial effects of host factors that govern the overall progression of HIV infection.